Das Spiel mit dem Zuschauer Die Bedeutungsgenerierung im polnischen Bildertheater am Beispiel von "Szczelina" Leszek Madziks, "Replika" Józef Szajnas und "Niech sczezna artyści" Tadeusz Kantors - Dobrowlanska-Sobczak, Monika Joanna (Slavistische Beitraege, 1999)
The focus of the present work is a semiotic analysis of the meaning generation in the picture theater, a stage form that decisively shaped the Polish theater of the last 40 years, which unmistakably draws its innovation and creativity potential from the fine arts, so that the desperate critics and spectators - in the case their most radical variants with their renunciation of the word and a strong repression of the actor - ask the question whether, strictly speaking, this is still a theater, or even a paratheatrical action in the field of visual arts